Effect of an educational intervention delivered to senior nursing students to strengthen spiritual care for people with chronic illness (2020)
This is an experimental, quantitative, parallel design study (control and experimental groups) with pre- and post-intervention assessment without blinding, which aimed to determine the effect of an educational intervention delivered to ninety Colombian senior nursing students to strengthen perceptions of spirituality and spiritual care for people with chronic illness. The Spirituality and Spiritual Care Rating Scale (SSCRS) was used as the instrument of measurement. The Wilcoxon test was used for comparisons between two groups, and the Kruskal-Wallis test for the comparison of global scale scores between the intervention group and the control group. To determine the effect of the intervention, Cohen’s d statistic was used. The intervention modified the perceptions of spirituality and spiritual care in the experimental group (median = 80.2, SD = 10.2) compared with their initial perceptions (median = 70, SD = 11.2), p ≤ 0.001. The effect size (ES) of the intervention was 0.63, with a power of 0.80, indicating a moderate and acceptable effect size.